(untitled) (Vietnam Journal of Community Medicine, 2021)
Objective: To assess the current situation of using drugs for treating Basedow disease on inpatients at Can Tho City General Hospital. Objects and methods: Retrospective study of over 70 medical records of Basedow patients for the first inpatient treatment, stored at the Steering Room of Can Tho City General Hospital from July, 1st, 2020 – September, 30th, 2020. Results: All patients used synthetic antithyroid drugs. β blockers accounted for 91.43%. The group of drugs supporting treatment accountsed for 97.14%, of which liver tonic accounted for the largest proportion of 97.14%. The majority of patients using a combination regimen of 3 drug groups for treatment accounted for 77.14%. Monotherapy regimen used at least 2.86%. Only 2.86% of patients used 1 drug of antithyroid group for treatment. The percentage of people had to change drugs for treatment was 10.0%. Conclusion: Synthetic antithyroid drug was a mandatory option for patients based on inpatient treatment. Mostly, patients needed to use a 3-drug combination regimen for treatment. The proportion of people had to change the treatment regimen accounted for a low rate.